Extremely High Power Efficiency Solution‐Processed Orange‐Red TADF OLEDs via a Synergistic Strategy of Molecular and Device Engineering. Issue 6 (22nd January 2022) - Jiang, Dehao; Sasabe, Hisahiro; Arai, Hiroki; Nakao, Kohei; Kumada, Kengo; Kido, Junji
Abstract: The development of high‐performance, solution‐processed, orange‐red organic light‐emitting diodes (OLEDs) based on thermally activated delayed fluorescence (TADF) emitters is a challenging endeavor. In this study, two orange‐red TADF emitters, namely 2DMAC‐DBP‐2 t BuCz and 2SPAC‐DBP‐2 t BuCz, are developed by a novel donor–acceptor–functional‐group (D‐A‐R) molecular design strategy. This design makes the molecules highly soluble and inhibits concentration quenching of excitons, rendering the emitter suitable for use in devices with high concentration to boost their performance. The solution‐processed, orange‐red OLEDs manufactured in this study achieve a state‐of‐the‐art maximum external quantum efficiency ( EQE max ) value of 23.7% and an extremely high maximum power efficiency ( PE max ) of 48.8 lm W −1, which is nearly twice higher than the previously reported best value (27.1 lm W −1 ). Therefore, the collaboration of molecular engineering and sophisticated device design provides a novel method for extremely low power consumption solution‐processed OLEDs. Abstract : In this study, two orange‐red TADF emitters are developed by a novel donor–acceptor–functional‐group (D‐A‐R) molecular design strategy. This design makes the molecules highly soluble and inhibits concentration quenching of excitons. By optimizing the device structure, the solution‐processed, orange‐red OLEDs achieve a record‐high maximum external quantum efficiency of 23.7% and an unprecedented‐high maximum power efficiency of 48.8 lm W −1 .